2009
DOI: 10.1007/s00244-009-9334-7
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Four Emergent Macrophytes to Remediate Permethrin in Mesocosm Experiments

Abstract: Increased focus is being placed on the ability of native vegetation to mitigate potential harmful effects of agricultural runoff, especially pyrethroid insecticides. Replicate 379 L Rubbermaid tubs (1.25 m [l] 9 0.6 m [w] 9 0.8 m [h]) were planted with individual species of cutgrass (Leersia oryzoides), cattails (Typha latifolia), burreed (Sparganium americanum), and powdery alligator-flag (Thalia dealbata), all common wetland macrophytes found in the Mississippi Delta, USA, agricultural region. Permethrin-enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 31 publications
1
10
2
1
Order By: Relevance
“…Plant-specific mitigation of cis-permethrin in aquatic mesocosms ranged from 67% reduction with Typha latifolia L. to 71% reduction with Leersia oryzoides (L.) Sw. [33]. Within this same study, however, there was no significant difference in permethrin mass mitigation between different plant species and the unvegetated control [33]. The short hydraulic retention time (4 h) was likely the main factor for this lack of discrepancy.…”
Section: Tomato Field Ditchcontrasting
confidence: 56%
See 1 more Smart Citation
“…Plant-specific mitigation of cis-permethrin in aquatic mesocosms ranged from 67% reduction with Typha latifolia L. to 71% reduction with Leersia oryzoides (L.) Sw. [33]. Within this same study, however, there was no significant difference in permethrin mass mitigation between different plant species and the unvegetated control [33]. The short hydraulic retention time (4 h) was likely the main factor for this lack of discrepancy.…”
Section: Tomato Field Ditchcontrasting
confidence: 56%
“…Schmitt et al [32] reported that filter strips comprising trees, shrubs, and grasses at widths of 7.5 m and 15 m reduced permethrin-associated contaminants by 27 to 83%. Plant-specific mitigation of cis-permethrin in aquatic mesocosms ranged from 67% reduction with Typha latifolia L. to 71% reduction with Leersia oryzoides (L.) Sw. [33]. Within this same study, however, there was no significant difference in permethrin mass mitigation between different plant species and the unvegetated control [33].…”
Section: Tomato Field Ditchcontrasting
confidence: 47%
“…As in the case of other insecticides, the presence of permethrin has been reported in the water bodies receiving run-off, in the United States and the United Kingdom. Permethrin when received in an aquatic system is potentially harmful to the fauna and flora (Moore et al 2009). Hence, the washing of the impregnated uniforms in river water should be discouraged, and the wash water needs to be properly disposed so as to prevent contamination of the environment.…”
Section: Resultsmentioning
confidence: 99%
“…processes in VTS. Beyond that, the ability of aquatic macrophytes to eliminate pesticides from the aqueous phase has been investigated at the laboratory (Crum et al 1999;Olette et al 2008), microcosm (Bouldin et al 2005), and mesocosm scale (Moore et al 2009). Furthermore, Passeport et al (2011) determined high coefficients for pesticide adsorption to wetland plants and forest litter followed by compound-related desorption.…”
Section: Introductionmentioning
confidence: 99%